(untitled) (مجلة البيان العلمية, 2023)
Globally, one of the diseases of economic impact and that affects the goat is Caprine Arthritis Encephalitis (CAE) caused by a virus of the Retroviridae family, genus Lentivirus, a group belongs to the Human Immunodeficiency Virus (HIV) and Ovine Progressive Pneumonia Virus (OPPV). Caprine Arthritis Encephalitis are a contagious febrile viral disease affecting the goats of all breeds, age or sex. CAE causing acute encephalitis, chronic non-suppurative arthritis of the tarsal, carpal joints, enlarged and severe hardening of the udder (indurative mastitis), with a bilateral nature that causes hypo or agalaxia, hypertrophied retromammary lymph nodes and chronic pneumonia. Caprine Arthritis Encephalitis Virus (CAEV) like all lentiviruses, has a diameter of 80-130nm enveloped particles with a dense conical nucleus, contains two copies of single-stranded genomic RNA and several viral proteins with positive polarity characterised by an extreme slowness of it is replication processes. The virus is very closely related to the Maedi-Visna Virus (MVV) which causes a very similar disease in sheep. Management and hygiene at the level of milking equipment and utensils are common act to more than one individual can reduce the transmission of contagious agalaxia in a herd. Newborns should be fed colostrum from uninfected females or with pasteurized milk. Cleaning and regular disinfection of pens are sanitary measurements planned as a prevention strategy.